Characteristics Associated With Treatment Failure 1 Year After Midurethral Sling in Women With Mixed Urinary Incontinence. Issue 2 (February 2021) - Sung, Vivian W.; Richter, Holly E.; Moalli, Pamela; Weidner, Alison C.; Nguyen, John N.; Smith, Ariana L.; Dunivan, Gena; Ridgeway, Beri; Borello-France, Diane; Newman, Diane K.; Mazloomdoost, Donna; Carper, Benjamin; et al.
Abstract : (Abstracted from Obstet Gynecol 2020;136:482–491) Mixed urinary incontinence, including both stress urinary incontinence (SUI) and urgency urinary incontinence (UUI), occurs in up to 50% of women with urinary incontinence. Mixed incontinence is often considered more severe and more difficult to treat than either urinary condition alone.